Okoliczności zwołania Soboru Nicejskiego - Grzywaczewski, Józef (Vox Patrum, 2014)
The article presents the circumstances of the Council of Nicaea. There was a tradition to compose symbols of the faith (symbola fidei), and to organize synods. The Council of Nicaea was convoked by Emperor Constantine in cooperation with Pope Silvestre. After the victory on Licinius, Constantine wanted to arrange public and religious matters of the Empire. He was not a Christian but he was friendly to Christianity as a religion which he considered to be profitable for the Empire. He possessed the title of Pontifex maximus which authorized him to intervene not only in pagan cults, but also in ecclesiastical affaires. In spite of that, there were three main conflicts in that time: the date of the Passover, Donatism and Arianism. Donatism was a schism born in Latin Africa having a national background; it was a movement of the local population against the Roman administration. Arianism, born in Greek Africa, was inspired by philosophy, especially by Neo-Platonism. Constantine was welcomed by the Pope and other bishops because his actions were useful for the Church. People were waiting for the Council of Nicaea with hope.